2013
DOI: 10.1186/1471-2458-13-492
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of suicidal behaviour in 36,304 individuals sickness absent due to stress-related mental disorders - a Swedish register linkage cohort study

Abstract: BackgroundStress-related mental disorders (SRMD), which correspond to the diagnostic code F43 in the International Classification of Diseases, version 10, rank among the leading causes of sickness absence in several European countries. Despite the size of this health problem, research on risk factors for severe medical outcomes, like suicidal behavior, is lacking to date. The aim of this study was to investigate predictors of suicide attempt and suicide among sickness absentees with SRMD.MethodsA cohort of 36,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
6
16
0
1
Order By: Relevance
“…The study complements research done in other countries (Andres, Collings, Qin, 2010;Brown, Beck, Steer, & Grisham, 2000;Arria et al, 2009;Brown et al, 2000;Khan, Leventhal et al, 2002;Sareen, Cox, Afifi, de Graaf, Asmundson, et al, 2005;Have, de Graaf, van Dorsselaer, Verdurmen et al, 2009;Crump, Sundquist, Sundquist, Winkleby, 2013;Ishtiak-Ahmed, Perski, Mittendorfer-Rutz, 2013). The present study showed that: 1) Unwillingness to live was more expressed in Lithuanian women than in men.…”
Section: Discussionsupporting
confidence: 63%
“…The study complements research done in other countries (Andres, Collings, Qin, 2010;Brown, Beck, Steer, & Grisham, 2000;Arria et al, 2009;Brown et al, 2000;Khan, Leventhal et al, 2002;Sareen, Cox, Afifi, de Graaf, Asmundson, et al, 2005;Have, de Graaf, van Dorsselaer, Verdurmen et al, 2009;Crump, Sundquist, Sundquist, Winkleby, 2013;Ishtiak-Ahmed, Perski, Mittendorfer-Rutz, 2013). The present study showed that: 1) Unwillingness to live was more expressed in Lithuanian women than in men.…”
Section: Discussionsupporting
confidence: 63%
“…The lifetime risk of suicide is around 4-15% for patients with depressive disorders (Guze and Robins, 1970;Blair-West et al, 1997;Inskip et al, 1998;Nordentoft et al, 2011). Suicide attempts occur more frequently than completed suicides and the lifetime risk among patients with depressive disorders is estimated to be 8-17% (Isometsa et al, 1994;Sokero et al, 2005;Vuorilehto et al, 2006;Hawton and van Heeringen, 2009;Riihimaki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mental disorders, particularly depressive disorders, are one of the largest diagnostic groups behind sickness absence, especially long-term sickness absence (Hensing and Wahlström, 2004;Waddell and Burton, 2006;OECD, 2013) and may increase the risk of permanent occupational disability and granting of disability pension (Järvisalo et al, 2005;Gjesdal et al, 2008;Danielsson and Berlin, 2012), and mortality (Kivimaki et al, 2003;Mittendorfer-Rutz et al, 2012). Recent studies have reported higher risks for suicide attempt as well as suicide among people having sickness absence in general as well as due to specific diagnoses (Qin et al, 2000(Qin et al, , 2003Vahtera et al, 2004;Melchior et al, 2010;Jansson et al, 2012;Ishtiak-Ahmed et al, 2013;Wang et al, 2014), including sickness absence due to affective disorders .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations